Noma recurrence in an adult: A case report from the Noma Children Hospital, Sokoto, Nigeria - Mujtaba Bala; K. Hakki Karagozoglu; Ramat Oyebunmi Braimah; Abdurrazaq Olanrewaju Taiwo; Ibrahim Kayode Suleiman; Abubakar Abdullahi Bello (Oral and Maxillofacial Surgery Cases)
Noma, also known as gangrenous stomatitis, is a devastating gangrenous infection of the mouth that predominantly affects children living in the poorest regions of the world. Although rare, noma can also affect adults, particularly those who are immunocompromised. Controversy exists about whether noma can recur. We report a case of a 65-year old man with recurrence of noma symptoms 2 years after his initial presentation. The patient responded well to antibiotic therapy, supportive care and serial debridement. This case demonstrates that noma can recur in adults, even after successful treatment of the initial treatment.